Pelatihan Pengajaran Menggunakan Model Pembelajaran Diagnosa untuk Meningkatkan Kemampuan Pengajaran Guru - Vivin Krismawati Modjanggo; Ika Paramitha Lantu; Yuliana Daeng Macora (Mosintuwu Jurnal Pengabdian Kepada Masyarakat, 2021)
In order to improve the quality of learning in the classroom, teachers need to develop their skills in applying learning methods in the learning process. Based on existing observations, many teachers still do not use learning methods in the learning process in class. Departing from this, this program aims to introduce the diagnostic learning methods to BOC (Body of Christ) Kids PAUD teachers hence that they can be used to improve the teaching quality. This learning method is introduced through training which was carried out for 2 (two) days by the head of the implementation team to improve the professional competence of BOC Kids PAUD teachers. This activity runs with the help of two implementing members. After participating in this training activity, the teachers are expected to be able to apply the strategies that have been obtained during the training to students in the class. It is hoped that teachers and students can improve the quality of good learning.